Development of Teaching Material of Sony Vegas Media Based with Anchored Instruction Models for Tennis Course in IKIP Budi Utomo Malang - Susanto, Ratno; Riyanto (Proceeding International Conference on Science and Engineering, 2020)
The purpose of this study is to develop teaching materials of Sony Vegas media based with anchored instruction models. The development of this teaching material used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Dessiminate). This research was started from the define stage where at this stage identification of material concepts were carried out in the textbook. Furthermore, the design and manufacture of Sony Vegas media based teaching materials with anchored instruction models was carried out in the design phase. After the teaching materials have been designed and made, the development stage was carried out, namely product validation by experts and product trials in the lecture process. Based on the results of this develop phase, it can be stated that the product was valid and practical, so it can be continued to the dessiminate stage. Based on the results of the validation of media experts, material experts, and small group trials. As a whole the development of teaching material with Soni Vegas-based is appropriate to be used as teaching material with an average value of 96.17% and it includes in the criteria of "Very Valid”.